Clinico-Epidemiologic Study Of Acute Respiratory Tract Infections Among The Student Community Of Universiti Putra Malaysia - Jamal, Dr.ezra (2002)
Acute respiratory tract infections (ARI) are commonly encountered. Although usually self-limiting in young and working adults, their economic burden is enormous. Currently, published data on epidemiology of ARI among Malaysian adults is lacking particularly in general practice setting. The present clinicoepidemiological study was carried out with this in view. The study of ARI among the Universiti Putra Malaysia (UPM) student community was carried out for a period of one year ( 1998), following the guidelines set by WHO. Students attending the Student Health Center (SHC) of UPM with the complaints of ARI between the ages 17-40 years were included. An illness was considered to be an ARI if at least three of the following complaints were present: running or blocked nose, phlegm (post nasal drip), sore throat or difficulty in swallowing, fever or body pain, ear pain or discharge, hoarseness of voice, headache and cough of less than one week duration with or without sputum and with or without difficulty in breathing.